Pengaruh Penghasilan, Pengalaman Masa Lalu, Ulasan Pelanggan, Rating Toko terhadap Keputusan Beli Pelanggan Tiktok Shop - Leo Allerio Edward Paruhum Pasaribu; Sih Mirmaning Damar Endah (Faculty of Economics and Business, Jenderal Soedirman University, 2025)
This study investigates the impact of past experience, online customer reviews, and store ratings on customer purchase decision in the context of TikTok Shop. Along with the development of e-commerce, platforms such as TikTok Shop have emerged as important players, combining social media engagement with direct purchasing options. This research aims to understand how these factors influence consumer behavior and decision-making processes. Past experience refers to customers' previous interactions and transactions on the platform, which shape their level of trust and satisfaction. Online customer reviews provide social proof and insights into product quality and seller reliability, which influence potential buyers. Store ratings, a summary of overall customer satisfaction, serve as a quick reference to evaluate a seller's credibility. This research contributes to the understanding of consumer behavior in social commerce environments and offers practical implications for sellers looking to optimize their strategies on TikTok Shop. By capitalizing on past positive experiences, encouraging customer reviews, and maintaining.